THE ROLE OF TEACHERS IN REALIZING INCLUSIVE EDUCATION FOR CHILDREN SPECIAL NEEDS AT SMP NEGERI 03 KARANGANYAR: PERAN GURU DALAM MEWUJUDKAN PENDIDIKAN INKLUSI BAGI ANAK BERKEBUTUHAN KHUSUS DI SMP NEGERI 03 KARANGANYAR - Indah, Annisa (JPI (Jurnal Pendidikan Inklusi), 2025)
This research discusses the role of teachers in realizing inclusive education for Children with Special Needs (ABK) at SMP Negeri 03 Karanganyar. Through qualitative approaches and triangulation techniques, data was obtained from observation, interviews, and documentation. The results of the study show that teachers play the role of facilitators, motivators, evaluators, and collaborators. The strategies used include differential learning, individualized instruction, the use of visual media, and adaptive classroom management. Teachers also work with psychologists, BK teachers, and parents to accompany ABK as a whole. The obstacles faced include the lack of physical facilities, the lack of optimal assistive technology, and the absence of mentoring programs. Nevertheless, the commitment and competence of teachers are the main factors for the success of inclusive education. This research recommends ongoing training, improved facilities, and cross-professional collaboration to support the right to learn in a fair and meaningful manner.